Acquired angioedema in B cell lymphoproliferative disease: A retrospective case series. (11th October 2021) - Wonnaparhown, Alex; Stefanovic, Alexandra; Lugar, Patricia; Hostetler, Haley P.
Abstract: Acquired angioedema due to C1‐inhibitor (C1‐INH) deficiency (AAE‐C1‐INH) is rare and is associated with underlying lymphoproliferative diseases. C1‐INH deficiency may be due to neoplastic over‐consumption of C1‐INH and the generation of anti‐C1‐INH autoantibodies. Uncovering an occult malignancy can lead to earlier oncology referral and improvement of angioedema after treatment of the underlying lymphoproliferative disorder. We characterized seven patients with C1‐INH‐AAE that highlights the importance of recognizing the association between C1‐INH‐AAE and underlying malignancy. In acute attacks, patients may be resistant to C1‐INH therapy due to the presence of anti‐C1‐INH autoantibodies or rapid complement consumption, and may respond better to icatibant or ecallantide, which directly affect bradykinin. Treatment of the underlying malignancy also improves AAE‐C1‐INH symptoms and supports the role of lymphoproliferative B cells in AAE‐C1‐INH pathophysiology. Monitoring levels of C4, C1‐INH function and level, and C1q may be predictive of AAE‐C1‐INH control and be used as surrogates for treatment efficacy. With close monitoring, low‐dose danazol can be effective for long‐term prophylaxis. Annual evaluation in AAE‐C1‐INH is recommended if an underlying malignancy is not found, as angioedema may precede the development of malignancy by several years. Our single‐center study has aided in standardization of comprehensive AAE‐C1‐INH diagnosis, treatment, and monitoring strategies towards future therapeutic clinical trials.